Validasi Instrumen Eksplorasi Etnomatematika pada Rumah Adat Lontiok Kabupaten Kampar - Agustina, Sinta; Ediputra, Kasman; Zulfah, Zulfah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
This study aims to determine the validity of the instrument used in ethnomathematics exploration research at the traditional house of Lontiok, Kampar Regency. The subjects of this study were 3 validators who are experts in their fields. This study uses validity instruments. The research data was collected using an interview validation sheet. Based on the results of the validation of the interview sheet using instrument validation, the validator stated that the interview sheet was in a very valid category, so that the interview sheet could be used to obtain data and information for research needs.